New directions in regional economic development : the role of entrepreneurship theory and methods, practice and policy - Desai, Sameeksha; Nijkamp, Peter; Stough, Roger (Cheltenham : Edward Elgar, 2011)
The book's contributions amplify understanding of such critical issues as the relationship between innovation and entrepreneurship, the entrepreneur's role in transforming knowledge into something economically useful, and knowledge commercialization with both conceptual and empirical contributions
pt. 1. Theory and methods in entrepreneurship and development -- pt. 2. Case studies including practice and policy.
&#x000A
Includes bibliographical references.
nif 15/05/13
Loans
Keywords: Regional economics; Economic development; Entrepreneurship; Entrepreneurship -- Case studies; Endogenous growth (Economics)